Character association and path analysis in sunflower (Helianthus annuus L.): CHARACTER ASSOCIATION AND PATH ANALYSIS IN SUNFLOWER - V PRABHAKARAN; S MADHUSUDHAN REDDY; T DAYAKAR REDDY; A R G RANGANATHA (Journal of Oilseeds Research, 2013)
Association and path coefficient analysis was computed on 64 genotypes of sunflower (Helianthus annuus L.). Seed yield was positively correlated with number of filled seeds/head, total number of seeds/head, seed filling per cent, plant height and 100 seed weight. Selection based on number of filed seeds/head, total seeds/head and seed filling percent would increase seed yield. Path analysisindicated that number of filled seeds/head had the maximum direct effect followed by 100 seed weight, total seeds/head and seed filling per cent.